FORMATION OF THE PRIMARY SCHOOL TEACHER`S INFORMATION COMPETENCE IN THE CONDITIONS OF THE INFORMATION AND COMMUNICATION PEDAGOGICAL ENVIRONMENT - Vinnyk Тетяна (Journal of Information Technologies in Education (ITE), 2021)
Considering the modern society`s requirements to the educational system, the necessity of its` constant updating and continuity, there is an urgent need to change the priority goals of the educational institutions` activities, the primary school in particular. The readiness of the students to use information and communication technologies, ability to work with information should be one of the results of education. The peculiarity of the professional activity of a primary school teacher is that it helps students to adapt to the educational environment, implements the developmental function of learning in the conditions of information and communication pedagogical environment of the school. Consequently, the main task of the teacher is the introduction into teaching practice of different approaches and methods of teaching primary school students, integration into the educational process of modern information and communication technologies. The quickness of active formation of information and communication pedagogical environment of the New School, the introduction of various software and hardware, technologies of search, collection, analysis and processing of information, the transition to the distance learning under pandemic conditions significantly exceeds the quickness of the formation of teacher readiness to use new approaches and technologies. This confirms the relevance and necessity of researching the methods and means of formation of the primary school teachers` information competence in the information and communication pedagogical environment. This problem should be solved by the assessment of the level of information competence of students majoring in Primary Education, review of review of educational programs and plans, teaching and methodological support, introduction into the educational and research process of modern methods, forms and means of teaching. Accordingly, the key tasks of this article are defining the main problems of the formation of information competence of primary school teachers in the information and communication pedagogical environment, studying the level of information competence students of the specialty 013 Primary Education, review and analysis of existing tools and approaches to the educational process in the conditions of distance learning that can be integrated into the educational process, and, subsequently, used by future teachers in practice.